The motivating factors to study the case of the Muslim students in University of the Phlippines, Diliman - Hadji Abdul Racman, Sohayle M. 1982 (2006)
seeks to uncover the underlying reasons of the Muslim's students willingness to be temporarily uprooted from their home provinces in Mindanao to pursue college education or some other reason would be like to have further enhance their education in the University of the Philippines, Diliman...
Vita.
"April 2006."
Thesis (M.A. Islamic Studies)--University of the Philippines Diliman.
Keywords: University of the Philippines (Diliman) -- Students, Muslim; Muslim students -- Education -- Philippines